PENGARUH PRODUK, PROMOSI, DAN CITRA MEREK TEHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA (Studi Empiris Pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank Semarang) (Students' Journal of Economic and Management, 2015)
This study aims to determine the effect of the product, promotion, brand image together or partially on purchasing decisions Yamaha motorcycle. The data used in this research is the primary data, with the questionnaire as a research instrument, which is then processed by calculation SPSS (Statistical Product and Solutions) version 19. The population in this study is the Faculty of Economics and Business, which uses Yamaha motorcycle at the University Stikubank Unisbank Semarang, which amounted to 100 respondents. The sampling technique in this study using purposive sampling intentional sampling according to peprsyaratan samples required. The analysis tool used is multiple linear regression. The results showed that there was a significant positive influence on purchasing decisions among products. There is a significant positive influence between promotion on purchase decisions. There is a significant positive effect between brand image on purchase decisions. Keywords: product, promotion, brand image, and purchasing decisions